Pengaruh Zakat Produktif dan Minat Berwirausaha Terhadap Peningkatan Pendapatan Masyarakat Miskin Pada BAZNAS Kota Gorontalo - Andi Mardiana; Agustin Y Lihawa (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
In this research, writer to use quantitative method that is research wish to explain influence relationship and difference between variable X1 (Zakat Earning), X2 (interest of entrepreneurship) and variable Y (People Income) at baznas in Gorontalo city. The population in this research is 250 benefic of productive zakat and the samples are 71 samples. Method of sampling by random sampling. Sources of data in this study are primary data and secondary data. Zakat productive and entrepreneurial interests simultaneously have a positive and significant effect on increasing the income of poor people in Baznas KotaGorontalo. It is obtained from the test result f that is fcount of 17,597 with significant level 0.000 and ftabel = 3,13 with significant level 0,05, and also R Square value equal to 0,341 or 34,1%. In this case means that productive and entrepreneurial zakat affect the increase in income of the poor by 34.1%, while the rest of 65.9% influenced by other variables not examined in this study